2006
DOI: 10.1007/s11205-005-4857-4
|View full text |Cite
|
Sign up to set email alerts
|

Hope and Adaptation to Old Age: Their Relationship with Individual-Demographic Factors

Abstract: adaptation to old age, hope, individual differences,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 26 publications
2
12
0
5
Order By: Relevance
“…Being in good physical condition allows the elderly to achieve their goals (Moraitou et al, 2006). Those in our sample regard their life as meaningful in all three categories (Table 2).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Being in good physical condition allows the elderly to achieve their goals (Moraitou et al, 2006). Those in our sample regard their life as meaningful in all three categories (Table 2).…”
Section: Discussionmentioning
confidence: 91%
“…In brief, this type of education has preventive, rehabilitative and activating functions, besides affecting health in a positive way (Špatenková, Smékalová, 2015). In our study, we investigated the presence of salutogenic factors of mental health, such as meaningfulness, experience of emotional well-being, and hope (Moraitou et al, 2006;Ondrušová, 2010). Negative indicators, such as experience of loneliness or depression, were also studied.…”
Section: Discussionmentioning
confidence: 99%
“…Para un trabajo previo, el segundo autor tradujo al griego la ADHS (Moraitou, Kolovou, Papasozomenou, y Paschoula, 2006). Los participantes debían contestar si cada uno de los 12 ítem eran cierto sobre ellos mismos, en una escala de 5 puntos tipo Likert, desde 1 (nada cierto) al 5 (muy cierto) y no en la escala de 8 puntos propuesta por Snyder et al (1991; ver también Moraitou et al, 2006).…”
Section: La Adult Dispositional Hope Scale (Adhs) [Escala De Disposicunclassified
“…Los participantes debían contestar si cada uno de los 12 ítem eran cierto sobre ellos mismos, en una escala de 5 puntos tipo Likert, desde 1 (nada cierto) al 5 (muy cierto) y no en la escala de 8 puntos propuesta por Snyder et al (1991; ver también Moraitou et al, 2006). El análisis factorial confirmatorio ratíficó la estructura de dos factores de la ADHS para esta muestra, o sea, factores de Waypower ('Pensamiento orientado a caminos') y Fuerza de Voluntad ("Pensamiento orientado a la Agencia"), χ 2 (19, Ν = 275) = 60,30, p < ,001, χ 2 /df = 3,44, CFI = ,907, SRMR = ,065, RMSEA = ,089 (CI 90% ,064 a ,115), (ver Brown, 2006).…”
Section: La Adult Dispositional Hope Scale (Adhs) [Escala De Disposicunclassified
“…The concept of hope has been related to various benefits, and several studies have found a positive association between hope and well-being (Alarcon, Bowling & Khazon, 2013;Magaletta & Oliver, 1999), life satisfaction, meaning in life (Feldman & Snyder, 2005), psychological adjustment (Chang & DeSimone, 2001;Moraitou, Kolovou, Papasozomenou & Paschoula, 2006), coping with illness (Affleck & Tennen, 1996;Snyder, Lehman, Kluck & Monsson, 2006;Stanton, Danoff-Burg & Huggins, 2002;Berendes et al, 2010;Kortte et al, 2012), and therapeutic improvement (Irving et al, 2004). Snyder et al (1991) developed both a theory of hope and a measurement instrument, the "Dispositional Hope Scale" (DHS), which has been highly employed in research, mainly as a 3 measure of positive future thinking.…”
Section: Introductionmentioning
confidence: 99%